Literacy and Text Reading in Middle and High School Social Studies and English Language Arts Classrooms. Issue 3 (3rd May 2016) - Swanson, Elizabeth; Wanzek, Jeanne; McCulley, Lisa; Stillman-Spisak, Stephanie; Vaughn, Sharon; Simmons, Deborah; Fogarty, Melissa; Hairrell, Angela
Abstract : This study reports vocabulary and reading comprehension instructional practices implemented in middle and high school social studies and language arts classrooms. It also describes text reading practices. We conducted 137 observations of 11 social studies and 9 language arts teachers over the course of 1 academic year. We observed instructional practices supportive of vocabulary and reading comprehension to differing degrees in social studies and language arts. The proportion of time spent reading text was roughly the same across the 2 subjects, with differences by text type, reading mode, and grade level within both subject areas.